2010
DOI: 10.1203/pdr.0b013e3181f1ca99
|View full text |Cite
|
Sign up to set email alerts
|

Association of Birth Weight with Polymorphisms in the IGF2, H19 and IGF2R Genes

Abstract: There is a substantial genetic component for birth weight variation. We tested 18 single nucleotide polymorphisms (SNPs) in the IGF2, H19, and IGF2R genes for associations with birth weight variation in 342 mother-newborn pairs (birth weight 2.1-4.7 kg at term) and 527 parent-newborn trios (birth weight 2.1-5.1 kg) across three localities. SNPs in the IGF2R (rs8191754; maternal genotype), IGF2 (rs3741205; newborn genotype), and 5' region of the H19 (rs2067051, rs2251375, and rs4929984) genes were associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 42 publications
5
39
1
1
Order By: Relevance
“…Both IGF1 and IGF2 play a critical role in growth and have been linked to birth weight in genetic, epigenetic, and gene expression studies (Adkins et al, 2010;Heijmans et al, 2008;Koutsaki et al, 2011;McMinn et al, 2006;Ong et al, 2000;Straughen et al, 2015). Twin studies of IGF1 have found that intra-pair birth weight differences were significantly correlated with intra-pair IGF1 expression differences (Canpolat et al, 2011) and blood IGF1 concentrations (Westwood et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Both IGF1 and IGF2 play a critical role in growth and have been linked to birth weight in genetic, epigenetic, and gene expression studies (Adkins et al, 2010;Heijmans et al, 2008;Koutsaki et al, 2011;McMinn et al, 2006;Ong et al, 2000;Straughen et al, 2015). Twin studies of IGF1 have found that intra-pair birth weight differences were significantly correlated with intra-pair IGF1 expression differences (Canpolat et al, 2011) and blood IGF1 concentrations (Westwood et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we employed population genetic techniques to identify gene regions 1 The online version of this article contains supplemental material. exhibiting strong signatures of natural selection among Andeans and Tibetans from dense genome scan data (7,8).…”
Section: Study Participantsmentioning
confidence: 99%
“…Therefore, identifying the genetic and environmental factors contributing to IUGR is of particular interest for improving both perinatal and adult health. While recent studies have helped illuminate the role of maternal genetic variation on infant birth weight (1,21,60), much remains to be discovered with respect to the physiological pathways by which such genetic factors operate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Indeed, the IGF2 and H19 loci have been thought to influence birth weight and growth, though results are conflicting. 10 Bouwland-Both et al 11 recently examined a prospective birth cohort of SGA children in The Netherlands and compared them to children who were AGA at term. The authors extracted DNA from umbilical cord white blood cells, examined DNA methylation, and observed that decreased DNA methylation of IGF2DMR was present among SGA children.…”
Section: Perinatal Programming 1167mentioning
confidence: 99%